2012
DOI: 10.1504/ijsom.2012.047953
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of hotels by data envelopment analysis based on customers' perception and gap analysis

Abstract: The aim of this paper is to evaluate three, four and five-star hotels and to identify the most critical service quality dimensions in these hotels. This study applies the principle behind the SERVQUAL and performance methods to measure service quality of hotels. Yet, data envelopment analysis approach is exploited to evaluate the efficiency of hotels. Through identification of five SQDs and use of five-point Likert scale, two questionnaires containing 22 items were developed. The former questionnaire measure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Finally, technique for order preference by similarity (TOPSIS) was employed to rank the service quality and performance of Spanish chain hotels. Shirouyehzad et al (2012) used a Likert scale to evaluate the perceived and expected quality of customers; the key indicators used in their study were reliability, guarantees, service facilities, empathy, and staff responsiveness to customers. DEA was then used to evaluate the service performance of hotels and determine which hotels had benchmark services.…”
Section: Hotel Operations and Service Performance Evaluationmentioning
confidence: 99%
“…Finally, technique for order preference by similarity (TOPSIS) was employed to rank the service quality and performance of Spanish chain hotels. Shirouyehzad et al (2012) used a Likert scale to evaluate the perceived and expected quality of customers; the key indicators used in their study were reliability, guarantees, service facilities, empathy, and staff responsiveness to customers. DEA was then used to evaluate the service performance of hotels and determine which hotels had benchmark services.…”
Section: Hotel Operations and Service Performance Evaluationmentioning
confidence: 99%
“…However, Chou et al (2011) suggested that in Taiwanese airline and with Fuzzy weighted SERVQUAL method, “reliability” and “assurance” are highly important. In another Study, Shirouyehzad, Hossenzadeh Lotfi, Dabestani (2012) and Shirouyehzad, Lotfi, Shahin, Aryanezhad, Dabestani (2012) evaluated some three, four and five-star hotels in order to address the most important SQDs. The results revealed that “empathy” and “responsiveness” are the most important ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, customer satisfaction has a major impact on customer loyalty, price sensitivity, cross-buying and positive word-of-mouth (Shirouyehzad, Hossenzadeh Lotfi, Dabestani, 2012; Shirouyehzad, Lotfi, Shahin, Aryanezhad, Dabestani, 2012). Hence, it has become the common goal of all service organizations such as hotels and restaurants to satisfy their customers (Abdullah.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless SERVQUAL has been used most popularly in research as a generic tool to measure service quality of various services. While in some researches SERVQUAL has been modified by to suit the service settings (Rahman, 2005;Balaji and Ganesan, 2005;Davila et al, 2010;Newman, 2001;Stank et al, 1999;Chowdhary and Prakash, 2007;Nwabueze and Mileski, 2008;Khare, 2011) there are other researches where researchers have developed customised scales based on service setting on similar methodology as suggested by Parsuraman et al (1988), Shirouyehzad et al (2012), and Debata et al (2012).…”
Section: Service Qualitymentioning
confidence: 99%